DETEKSI KEBOHONGAN BERDASARKAN FITUR-FITUR SUPRASEGMENTAL: PENDEKATAN LINGUISTIK FORENSIK - Santoso, Budi (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2024)
This research was conducted to detect lies based on suprasegmental features from phonetic studies using a forensic linguistic approach. This research uses a qualitative method by applying experimental phonetics described in narrative form. Data collection was obtained from the results of interrogation which were stored in the form of recordings (wav. file). The interrogation was carried out after the determination of the research sample as many as three students (two men and one woman) who became suspects. Data processing used Praat voice analyzer software version 6.3.09 to display the suprasegmental features of speech that indicated lies. Based on the data processing, it was found that rapid intonation changes from rise to fall, or vice versa indicated a person's level of tension in speaking, as well as the presence of pauses in a longer duration and high voice frequency in the initial position of speech characterizes that someone commits lying.